A robust, systematic approach for developing the biodiversity sector's input for multi-sector Marine Spatial Planning. (1st November 2022) - Harris, Linda R.; Holness, Stephen D.; Kirkman, Stephen P.; Sink, Kerry J.; Majiedt, Prideel; Driver, Amanda
Abstract: As countries commit to developing their ocean-based economies sustainably, it is critical to secure the underlying marine biodiversity and ecological processes. Ecosystem-based Marine Spatial Planning (MSP) can support achieving this; however, because competition for ocean space is increasing, biodiversity prioritisation must be spatially efficient, conflict-averse, and robust to secure marine biodiversity appropriately. South Africa has a long history and real-world success in spatial planning on land; we aim to draw on this experience to develop an approach by which the biodiversity sector's input to MSP can be developed, in the context of MSP unfolding in South Africa. We used Marxan to develop the first National Coastal and Marine Map of Critical Biodiversity Areas (CBAs) and Ecological Support Areas (ESAs). There were 976 biodiversity features and design elements, and the cost layer aimed to avoid conflict with 19 sea-use sectors and avoid more heavily impacted areas. Biodiversity targets were met in 27.0% of the planning domain (5.4% Marine Protected Areas (MPAs), 21.6% CBAs), with 6.6% for ESAs. Sea-use guidelines were developed based on a matrix of activity compatibility with the management objective for CBAs (keep or restore to natural) and ESAs (avoid further degradation), with MPAs managed through their gazetted regulations. The CBA Map and sea-use guidelines formed the basis for the marine biodiversity sector plan for inclusion in MSP. This approach can be broadly applied, even with limited data, as the basis for multi-sector negotiations. We share seven recommendations from our experience to guide planners from other countries. Graphical abstract: Image 1 Highlights: A framework for developing the biodiversity sector's input to MSP is conceptualised. Efficient network of marine biodiversity priorities is identified for South Africa. Priorities comprise: MPAs; Critical Biodiversity Areas; Ecological Support Areas. Sea-use guidelines: based on activity compatibility with zone management objectives. Outputs are the basis for formal multi-sector stakeholder engagement.